The world makers: scientists of the Restoration and the search for the origins of the Earth - Poole, William (The past in the present, 2010)
Examines how the emerging discipline of experimental philosophy reacted to the Biblical Genesis to interpret the physical origin, present status, and final destination of Earth. Looks at the role of the Royal Society of London and men such as Isaac Newton, Robert Hooke, Edmond Halley, and Thomas Burnet in the developing separation of religion and science